Digital literacy and communication privacy in cybermedia era - Noerma Kurnia Fajarwati; Eka Susilawati; Rizqi Fitrianti; Putri Handayani; Meiby Zulfikar (Trigin Publisher, 2023)
The frenetic pace of technological advancements has altered how people interact with one another, including how frequently they access media. The purpose of this study is to examine the effects of digital literacy on communication privacy in the age of cybermedia. The research used SPSS analysis tools to conduct a quantitative approach and was based on communication privacy management theory. The study's subject was communication science students from Serang City universities, with a total of 200 respondents. The environment and socioeconomic status were found to play a significant role in the investigation of student communication privacy on social media. According to the findings of the research, the private space that exists in the age of cybermedia has encouraged individuals to interact with one another and become public consumption objects used by the media to generate reciprocity with the idea of profit and loss.